THE INFLUENCE OF DEBT POLICY AND PROFITABILITY ON COMPANY VALUE WITH DIVIDEND POLICY AS A MODERATION VARIABLE (STUDY ON COAL COMPANIES LISTED ON THE BEI) - Asra, Muhammad; Nur, Nuriman M (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This research aims to investigate the influence of Profitability, Debt Policy and Dividend Policy on Company Value, as well as evaluating whether Dividend Policy moderates the relationship between Profitability and Debt Policy and Company Value. Research data was analyzed using the Chow and Hausman tests to select the best model, as well as direct and indirect influence tests using the regression method and Sobel test. The results of the analysis show that Profitability has a negative impact on Dividend Policy, while Debt Policy does not have a significant direct influence on Company Value. Dividend Policy, on the other hand, shows a significant positive influence on Company Value. The Dividend Policy moderation test does not show a significant influence in moderating the relationship between Profitability and Debt Policy and Company Value. Thus, these findings indicate that in the context of this research, Dividend Policy plays an important role in shaping company value, while Profitability and Debt Policy are more likely to influence Dividend Policy than directly affecting Company Value. However, it is important to note that these conclusions may be influenced by the analysis methods and models used, as well as the specific characteristics of the research data. This research contributes to further understanding of the dynamics of corporate policy and corporate value in the context of corporate finance.Keywords:Debt Policy, Profitability, Company Value, Dividend Policy, Coal Companies, Indonesian Stock Exchange (BEI)